Effects on length of stay and costs with same-day retransfer to the referring hospitals for patients with acute coronary syndrome after angiography and/or percutaneous coronary intervention. Issue 4 (1st August 2016) - Andersen, Jack G; Grepperud, Sverre; Kløw, Nils-Einar; Johansen, Odd
Abstract: Background: Fast track interventions may generate benefits for patients and hospitals by representing a potential for shorter hospital stay. The aim of this study was to investigate how same-day retransfers to the referring hospital after angiographic examination and/or percutaneous coronary intervention (PCI) at the PCI centre affected length of stay and hospital treatment costs for patients with acute coronary syndrome. Methods and results: Three hundred and ninety-nine consecutive admitted patients were prospectively randomized to ordinary care with overnight stay or fast track with same-day retransfer. Length of stay at both the PCI centre and the referring hospital after the stay at the PCI centre were recorded. Costs at the PCI centre related to examinations and treatments were also collected. The ordinary care group included 206 patients and the fast track group 193 patients. Forty-six per cent underwent PCI and 10% coronary artery bypass graft (CABG) in the ordinary care group. In the fast track group 40% had PCI and 6% CABG. Length of stay was reduced at the PCI centre from a median 1.25 days for the ordinary care group to median 0.24 days for the FT group ( p <0.001). Length of stay at the PCI centre was significantly reduced after selective coronary angiography and PCI but not for patients undergoing CABG. No significant difference was identified in length of stay for the referring hospitals. Total median treatment costs were reduced from NOK23, 657 (US$3838) for the ordinary care group to NOK15, 730 (US$2552) for the fast track group ( p <0.001). The main contributor to this reduction was shorter length of stay and the corresponding reduction in ward costs at the PCI centre. Conclusions: We conclude that fast-track intervention with same-day retransfer for patients with acute coronary syndrome to the referring hospital reduced length of stay and the hospital treatment costs for patients undergoing selective coronary angiography and PCI.